Defects of Coffee Beans with Different Postharvest Processes and Roasting Temperatures on Volatile Compounds of Coffee Beans from Coffee Small-Scale Industries of West Lampung Indonesia - Analianasari, Analianasari; Berliana, Dayang; Shintawati, Shintawati (Trends in Sciences, 2024)
Specialty coffee is processed by performing high standards nationally (SNI) and internationally (SCAA). Good handling in the small coffee industry is essential to producing coffee raw materials as a refreshing drink. The aroma released from the best coffee beans gives an emotional flavor to the drinker - the aroma produced from the best coffee beans with different post-harvest methods. This study analyzed the physical quality of moisture content, coffee bean defects from dry processing post-harvest handling (natural and honey), and different roasting temperature differences to produce volatile compound profiles from three small-scale coffee industries. Six samples of raw materials from 3 small-scale coffee industries were selected by purposive sampling with the criteria that the processing farmer had performed SNI standards. Six coffee samples from the September harvest in 2022. Observations were made in the laboratory for analysis of moisture content and quality defects of coffee beans, then roasted by the industry and analyzed descriptively and multivariate analysis for volatile compounds. The moisture content of coffee beans from all coffee industries has met the requirements following SNI 01-2907-2008, that the moisture content is not more than 12.5 %. All coffee beans produced have 50 % potential as fine robusta coffee beans because they have no primary defects. Increasing the roasting temperature on all coffee beans increases volatile compounds. Coffee beans processed with honey produced more volatile compounds than the natural post-harvest method. The caffeine content in all post-harvest processing processes in the three industries has a difference in concentration due to differences in roasting temperature and time. The study that in the three-ground coffee small-scale industries processed by the natural post-harvest method, carbamic acid compounds were suspected to be from carbamate class insect pesticides (carbofuran) and the fungicide pyraclostrobin. Considering that pesticide residues harm human health, it is essential to implement measures to educate farmers to use organic fertilizers and ensure consumer safety. HIGHLIGHTS Coffee is a leading commodity of Lampung Province, Indonesia Defective coffee affects the quality of coffee beans The coffee produced by IKM is red cherry-picked Robusta coffee There have been findings of contamination from the chemical compound carbamate acid due to the use of herbicides/insecticides by farmers GRAPHICAL ABSTRACT